Members' Percieved Benefits and Values of the Association for International Agricultural and Extension Education - Rachel Garrett; Melanie Balinas; Gary Wingenbach; Tracy Rutherford; Kevin Fath; Samantha Alvis; Christopher Bielecki; Anna McGucken; Orry Pratt (Journal of International Agricultural and Extension Education, 2014)
The Association for International Agricultural and Extension Education (AIAEE) was established to strengthen and advance the knowledge base of agricultural and extension education worldwide. The purpose of this study was to determine perceived benefits of AIAEE membership. The objectives were to assess AIAEE members’ perceived organizational benefits; rank the top five perceived benefits; and, assign monetary values to the top five perceived benefits. AIAEE members (N= 161) responded to an online questionnaire. Respondents’ perceived organizational benefits included innovative ideas, professional knowledge, collaboration, opportunities to publish in the JIAEE (Journal of International Agricultural and Extension Education), and the importance of recognition awards. Their top five benefits were ranked as (a) journal, (b) conference, (c) networking, (d) professional development, and (e) communications. Lastly, they assigned monetary values to their AIAEE membership benefits. Values were highest for the journal (M = $25.06), followed by the conference (M = $21.94), and communications (M = $9.63). The AIAEE can recruit and retain members more effectively by continually evaluating members’ perceived benefits and values derived from membership. The AIAEE should create recruitment and retention plans based on members’ benefits and values, highlighting the most valuable and/or important benefits, and seek to strengthen lesser-valued benefits. As the AIAEE’s membership base changes, so too might change individual member’s perceived benefits and values, causing organizational shifts and/or priorities. For example, future AIAEE members may demand more social media interaction, instead of current communication mediums (i.e., journal, listserv, etc.)
Keywords: Membership Benefits; Values; Conference; Publications; Networking